Uma linguagem de modelagem de domínio específico para linhas de produto de software dinâmicas - Borelli, Helberth (2016)
Systems which involve adaptations due to context changes have the challenge of adapting software systems at runtime. This thesis adopts as proposal the adaptation of resources in the form of features, involving concepts of Feature Oriented Domain Analysis. A possible approach to develop systems based on adaptable features at runtime is the concept of Dynamic Software Product Line (DSPL), which can be implemented by Metamodels. The aim of this thesis is the development of a Domain Specific Modeling Language (DSML) for DSPL, designed from the construction of a metamodel for the development of DSPLs, which is divided in three metamodels: of features, of variabilities and of applications to derive products. The variabilities metamodel aims at modeling contracts that must negotiate the product adaptation to the features that may be present or not in the execution environment. Adaptations are based in state machines, which address changes of feature state or changes by transitions of equivalent features, in order to keep the execution of the software product. The developed DSML still plays the role of extending the constraints imposed by the metamodels, as well as to generate codes in general-purpose language based on modeling features, variabilities and applications. In order to validate the proposal, the DSML was used to model two DSPLs, including the derivation of products and the execution in a platform based in OSGi specification.